“I'm a bathroom expert”: a qualitative study exploring how students with physical disabilities manage toileting during college - Okanlami, Oluwaferanmi O.; Kreschmer, Jodi M.; Gupta, Saumya; Lee, Allison; Sarma, Aruna V.; Streur, Courtney S. (Frontiers in Pediatrics, 2024)
Health care providers caring for youth with physical disabilities encourage them to be as independent as possible, which includes obtaining higher education when feasible. However, little is known about the experiences of higher education students in managing their toileting. We performed 1:1 semi-structured interviews with 13 current college students with physical disabilities (4 male, 9 female), of whom six were on a formal bladder and/or bowel management program. Three researchers analyzed all transcripts using constructivist grounded theory procedures. We identified six themes, including: 1) adherence to prescribed programs, 2) importance of time management, 3) interfering with class, 4) balancing intake and toileting, 5) campus bathroom experiences, and 6) acclimating to new living situations. Students needed strong personal skills in time management, adaptability, and self-advocacy to both manage their toileting needs and engage in academic and social activities. This often took time to develop while in college. They faced barriers such as a lack of private, well-maintained bathrooms. Health care providers should encourage their patients to develop these personal skills prior to starting college, while colleges need to better support these students through honoring their accommodation needs and ensuring the availability of private, accessible bathrooms.